Research on IFC- and FDS-Based Information Sharing for Building Fire Safety Analysis - Jianyong Shi; Jicao Dao; Liu Jiang; Zeyu Pan (Advances in Civil Engineering)
With the development of computer processors, vast numerical simulation tools are widely used by fire engineers to determine the spread of fire and smoke. However, the fire modeling practices are often highly time-consuming and cost-intensive especially for building geometry information which does limit the further implementation of building fire safety analysis. Although nowadays building information modeling (BIM) has become a buzzword in the Architecture, Engineering, and Construction (AEC) field to facilitate information integration and interoperability, data sharing and exchange are still weak in the traditional interoperability between BIM applications and fire simulation software, since the data schema of them are totally different. In this paper, a quick and accurate approach for information sharing for building fire safety analysis between mainstream BIM applications and widely used fire simulation software has been successfully implemented, based on Industry Foundation Classes (IFC) and Fire Dynamics Simulator (FDS). And, both geometrical building information and sematic information can be shared by this approach through the transformation of coordinate systems, outer database, and IFC file extension. The BIM model restoring fire simulation results can support other performance-based design of building, such as structural fire-resistant design and evacuation design. And, all of the analysis results including building fire simulation, structure safety design, and evacuation simulation can be integrated in Autodesk Revit, establishing a framework of IFC- and FDS-based information sharing for building fire safety analysis successfully. A gymnasium has been taken as a case study to illustrate the capability of this framework.